A Case Report on DOORS Syndrome - Alexander, Sherin (Indian Journal of Pharmacy Practice)
DOORS syndrome is a genetic neurometabolic disorder. It is inherited as an autosomal recessive trait. It affects male and females in equal numbers. The main causes include TBC1D 24 mutations and genetic factors. Here we discuss a case of 11 year old boy diagnosed as DOORS syndrome with genetic cause. He was globally delayed in development and was frequently hospitalized due to recurrent seizure.
Keywords: DOORS syndrome; Genetic disorder; Dysmorphic features; TBC1D24 mutations; Neurometabolic disorder.